Philadelphia Translocation in MDS: A Case Report and a Brief Review of the Literature Looking at Its Prevalence, Disease Progression, and Treatment Options. (22nd November 2018) - Chelapareddy, Lakshmi Ramya; Sen, Sandeep
Abstract : Myelodysplastic syndrome (MDS) is a group of clonal disorders characterized by ineffective and dysplastic hematopoiesis in the bone marrow with variable risk of progression to leukemia. MDS is characterized by specific karyotypic and molecular abnormalities. The t(9 : 22) Philadelphia translocation is not a common abnormality found in MDS, and it is not included in the prognostic indices for germline mutations. There are no definitive treatment guidelines for these patients either. Here, we reviewed previously reported cases of MDS with the Philadelphia translocation with a goal to determine their prognosis and treatment options, specifically the tyrosine kinase inhibitors (TKIs).